Making waves: Wastewater-based epidemiology for COVID-19 – approaches and challenges for surveillance and prediction. (1st November 2020) - Polo, David; Quintela-Baluja, Marcos; Corbishley, Alexander; Jones, Davey L.; Singer, Andrew C.; Graham, David W.; Romalde, Jesús L.
Highlights: Presence of SARS-CoV-2 in feces and wastewater constitutes a paradigm shift in surveillance. WBE has potential as a surveillance and predictive tool during the COVID-19 pandemic. Validated protocols for concentration and quantification of SARS-CoV-2 and other markers are needed. Abstract: The presence of SARS-CoV-2 in the feces of infected patients and wastewater has drawn attention, not only to the possibility of fecal-oral transmission but also to the use of wastewater as an epidemiological tool. The COVID-19 pandemic has highlighted problems in evaluating the epidemiological scope of the disease using classical surveillance approaches, due to a lack of diagnostic capacity, and their application to only a small proportion of the population. As in previous pandemics, statistics, particularly the proportion of the population infected, are believed to be widely underestimated. Furthermore, analysis of only clinical samples cannot predict outbreaks in a timely manner or easily capture asymptomatic carriers. Threfore, community-scale surveillance, including wastewater-based epidemiology, can bridge the broader community and the clinic, becoming a valuable indirect epidemiological prediction tool for SARS-CoV-2 and other pandemic viruses. This article summarizes current knowledge and discusses the critical factors for implementing wastewater-based epidemiology of COVID-19. Graphical abstract: Image, graphical abstract